Polymer derived silicon oxycarbide ceramic monoliths: Microstructure development and associated materials properties. Issue 17 (1st December 2018) - Sasikumar, Pradeep Vallachira Warriam; Blugan, Gurdial; Casati, Nicola; Kakkava, Eirini; Panusa, Giulia; Psaltis, Demetri; Kuebler, Jakob
Abstract: Polymer derived SiOC and SiCN ceramics (PDCs) are interesting candidates for additive manufacturing techniques to develop micro sized ceramics with the highest precision. PDCs are obtained by the pyrolysis of crosslinked polymer precursors at elevated temperatures. Within this work, we are investigating PDC SiOC ceramic monoliths synthesized from liquid polysiloxane precursor crosslinked with divinylbenzene for fabrication of conductive electromechanical devices. Microstructure of the final ceramics was found to be greatly influenced by the pyrolysis temperature. Crystallization in SiOC ceramics starts above 1200 °C due to the onset of carbothermal reduction leading to the formation of SiC and SiO2 rich phases. Microstructural characterisation using ex-situ X-ray diffraction, FTIR, Raman spectra and microscopy imaging confirms the formation of nano crystalline SiC ceramics at 1400 °C. The electrical and mechanical properties of the ceramics are found to be significantly influenced by the phase separation with samples becoming more electrically conducting but with reduced strength at 1400 °C. A maximum electrical conductivity of 10 1 S cm −1 is observed for the 1400 °C samples due to enhancement in the ordering of the free carbon network. Mechanical testing using the ball on 3 balls (B3B) method revealed a characteristic flexural strength of 922 MPa for 1000 °C amorphous samples and at a higher pyrolysis temperature, materials become weaker with reduced strength.